Doubly periodic instanton zero modes - Ford, Chris; Pawlowski, Jan M. (Physics letters, 2005)
Fermionic zero modes associated with doubly periodic SU(2) instantons of unit charge are considered. In cases where the action density exhibits two ‘instanton cores’ the zero mode peaks on one of four line-segments joining the two constituents. Which of the four possibilities is realised depends on the fermionic boundary conditions: doubly periodic, doubly anti-periodic or mixed.